Noções de sujeito em modelos teóricos na Ciência da Informação: do enfoque no sistema à consideração da agência em contexto - Rabello, Rodrigo [UNESP] (Univ Fed Paraiba Ccsa, 2013)
Considering the investigating course of Information Science which, under different perspectives, admits theoretical constructions influenced by objective and/or subjective and/or social dimensions of information, this paper aims to identify conceptual elements about notions of user employed in modeling constructs in the area. For such, an investigation was made in a corpus comprised of 15 literature reviews on need, search, behavior and use of information published in the Annual Review of Information Science and Technology - ARIST. Corpus analysis allowed to illustrate the subject-object relation in traditional and alternative approaches, directed towards objective and subjective dimensions of information. It also allowed to propose systemic and emerging models, the latter comprising of the relative attraction of subjective and social dimensions. In the end, a table is outlined with results pointing towards the displacement and/or transcendence of the strict notion of subject, underlying as a singularity managing or using information in a system - then considering, complementarily, other possibilities for acting. In this direction, the subject is then conceived not only in terms of management or use actions, but also taking as fundament his/her agency in the process of appropriation and construction of information and knowledge, interactively and in context.
Notions of subject in theoretical models in information science: from focus on system to considering the agency in context
Keywords: Subject; Informational Agency; Theoretical Models; Epistemology; Information Science